DESAIN KOMUNIKASI DAKWAH VISUAL ANIMASI 2D UNTUK ANAK - Mokhamad Mahfud; Rama Kertamukti (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2016)
Dakwah activities as a communication process of delivering the teachings of Islam's ideal has no power to change people for the better. There are many causal factors, one of them is because of propagandas that has been done tends to be cold, impersonal, and is only informative sheer, yet using less effective communication ethics. A visual cultural revolution is now growing rapidly, unfortunately its dominated by capitalists and worshipers of lust. For example, nearly all visual ads is using the interest of sensuality and lust to lure customers. On the billboards, media newspapers, magazines, television and other media, visual communication seemed to be a valuable garbage, and this is very dangerous, especially if in the consumption of children who are mentally and immature psyche. The Effects of visual